Effect of Using the Perfect Learning Technique by Suggested Exercises (Perceptual - Kinetic Conciousness) For increasing theabilities of coincidence and agility in Basketball for young Players - Khlaf, Amer (Journal of Physical Education, 2015)
The successful of educating methods depends on multi techniques one of these technique calledbloom’s techniques that is required increasing the number of teaching unites and repetition of its exercises for taking the weak players more time in order to increase your results the exercises that is used nowdon’t use this technique because there aren’t more time to perfect the abilities of coincidence and agility and the less of teaching techniques and the repetition of it and the carelessness for all the excitiation and support sides so there is a new suggested exercises perceptual- kinetic consciousness depending on this technique and know Its effect through the pre and post results for the interest of the post, test while the post results of two groups for the interest of the testing group , so this technique proved to increase the two abilities for the testing group that is applied Exercises(Perceptual -kinetic consciousness) more than fixed group , the researcher said we should depend on this technique specially with the young group and make anew stadies like this mentioned anew abilities that is don’t mention in this research